A meta-analysis of the diagnostic value of microRNA for hypertensive left ventricular hypertrophy - Fei, Su-Hai; Liu, Zhen-Feng; Xie, Hai-Ning; Tong, Jia-Ni; Fang, Zheng-Mei; Chen, Yan; Yao, Ying-Shui (Frontiers in Cardiovascular Medicine, 2022)
In this study, the diagnostic value of microRNAs (miRNAs) for hypertension (HTN) with left ventricular hypertrophy (LVH) were evaluated by meta-analysis. A correlation study of the diagnostic value of miRNAs in HTN with LVH was conducted using a computer search of the China Knowledge Network (CNKI), Wanfang, VIP, China Biomedical Literature Database (CBM), PubMed, Web of Science, and Embase. Studies from the time of database creation to May 2022 were evaluated. The quality assessment of diagnostic accuracy studies-2 (QUADAS-2) tool in RevMan 5.3 was used to evaluate the quality of the literature, and Meta-Disc 1.4 and Stata 16.0, were used to calculate the combined sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic advantage ratio (DOR), and their 95% confidence intervals. Subject working characteristic curves were plotted and the area under the curve (AUC) was calculated using Stata 16.0. Seven publications and 8 studies were included. miRNA diagnoses of HTN with LVH had SENcombined = 0.84, SPEcombined = 0.80, PLRcombined = 4.2, NLRcombined = 0.20, DORcombined = 21, and AUCcombined = 0.89. Subgroup analysis showed that the sensitivity of plasma miRNA for the diagnosis of HTN with LVH was 0.85, which was higher than that of serum which was 0.83. The specificity of serum miRNA for the diagnosis of HTN with LVH was 0.82, which was higher than that of plasma which was 0.78, and the diagnostic accuracy of miRNA in serum DOR was 23, which was higher than that of plasma DOR which was 20. In the diagnosis of HTN with LVH, miRNA has high sensitivity and specificity and is a better biological marker.